Use of intrathecal morphine for analgesia in a surgical camp set up in Nepal - Shrestha, A.; Pradhan, B. (Journal of Institute of Medicine Nepal, 2007)
Background: Pain management is often inadequately addressed, especially in a mobile surgical camp set up. We try to look at an easier and effective method, i.e. intrathecal morphine for pain relief and it’s practicability in a camp set up. Method: 89 patients under going vaginal hysterectomy under spinal anesthesia were studied. They were randomly allocated to those receiving bupivacaine and intrathecal morphine (n=61) and another group receiving bupivacaine only (n=28). Their need for post operative analgesia and untoward effects like nausea/ vomiting, pruritis and respiratory depression were compared. Results: Significant pain relief was seen with the added intrathecal morphine but it also caused increased incidence of vomiting. Other serious effects were not seen. Conclusion: Intrathecal morphine is an effective method of post operative analgesia in operations under sub arachnoid block but an effective antiemetic cover is also required and vigilance to tackle any untoward effects is needed. Journal of Institute of Medicine Vol.27(3) 2005